AN ANALYSIS OF TURKISH AND ENGLISH FOREIGN LANGUAGE TEACHING BOOKS IN TERMS OF MULTICULTURALISM - Kara Özkan, Neşe (International Online Journal of Education and Teaching, 2022)
The research is carried out to determine multiculturalism in foreign language education. For this purpose “Yedi İklim Turkish Teaching Set” is used and in order to evaluate multiculturalism in English teaching “English File English Teaching Set” is used. What is in common for English File English and Yedi İklim Turkish Textbooks is that the elements of multiculturalism are mostly seen in values, beliefs and attitudes and national geography categories, in both. On the other hand, any element of multiculturalism in the body language category is not determined in both foreign language teaching sets. Moreover, it is seen that the number the multiculturalism elements in interpersonal relations category is very close to each other in both of the teaching sets. It is observed that the only category that Yedi İklim Turkish teaching set has more multiculturalism elements than English File English teaching set is ceremonial behaviors. It is found that English File textbooks include more multiculturalism elements in the categories of daily life, living conditions, social traditions and standardization than Yedi İklim Turkish textbooks. With reference to the findings of the research emphasized the importance of multiculturalism in foreign language teaching in the globalizing world, some suggestions are offered.